Explaining transformative change in EU climate policy: multilevel problems, policies, and politics. Issue 5 (4th July 2022) - Kreienkamp, Julia; Pegram, Tom; Coen, David
ABSTRACT: The EU's ambition to lead in global climate governance has shaped its engagement with the UNFCCC regime and informed a vast body of regulatory instruments. However, EU climate policy outcomes have not always matched aspirations. We explore how UNFCCC-EU institutional interactions have shaped EU climate policy outcomes by combining a multilevel governance perspective with scholarship on policy entrepreneurship to explain when, why, and how motivated policy entrepreneurs are most likely to secure transformative policy change. We contrast the successful policy transformation of the European Green Deal with the experience of policy stagnation in the aftermath of the economic crisis, shedding light on the interaction between problems, policies, and politics across levels. We find that while the international level is significant in opening up windows of opportunity from above, the presence below of an authoritative and motivated policy entrepreneur within the political stream is a crucial additive to securing transformative policy change.